2021
DOI: 10.31603/tarbiyatuna.v12i2.4996
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Parenting and Motivation from Parents and Its Influence on Children's Ability to Read the Quran

Abstract: The motivation of learners to learn the Qur'an in this day and age is very low, learners at the time to learn the Qur'an choose television activities, play games and others, therefore motivation from parents is needed to minimize the activities of learners who are less useful. Previous studies show that external factors affect Islamic children's development and ability to read the Quran. Therefore, this study aimed to determine how parenting techniques and motivation influence children's ability to read the Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
3
4
0
1
Order By: Relevance
“…On the other hand, technology will have a negative impact on children's development when children are left alone to operate technological devices without any assistance or supervision from their parents. The statement above is in accordance with the conclusion of Serdyukov who emphasized that technology does not always have a good impact on education (Serdyukov, 2017 ), Ritonga et al also emphasized that parents are the first school for children (Ritonga et al, 2022 ), Elvina et al also confirmed that participation active parents will make children successful in their education (Elvina et al, 2021 ).…”
Section: Resultssupporting
confidence: 80%
“…On the other hand, technology will have a negative impact on children's development when children are left alone to operate technological devices without any assistance or supervision from their parents. The statement above is in accordance with the conclusion of Serdyukov who emphasized that technology does not always have a good impact on education (Serdyukov, 2017 ), Ritonga et al also emphasized that parents are the first school for children (Ritonga et al, 2022 ), Elvina et al also confirmed that participation active parents will make children successful in their education (Elvina et al, 2021 ).…”
Section: Resultssupporting
confidence: 80%
“…Based on data and discussions with several expert opinions, students at Tbong Khmum Cambodia Muhammadiyah Education Center do not yet have high motivation in learning Arabic and Islam . On the one hand, this reality is caused by the lack of strong encouragement from parents, even though as emphasized by academics based on the results of the study, the motivation of students can be increased by the active role of parents (Elvina et al, 2021). Thus, increasing the motivation of students to learn Arabic and Islam can be performed by involving various parties.…”
Section: Asking To Gain Understandingmentioning
confidence: 98%
“…Furthermore, parents also become facilitators for children and have an obligation to nurture (hadlanah), which is to provide nurturing and care in the form of supervision of the child's physical and spiritual (Elvina & Lahmi, 2021;Kosim et al, 2022). Children have the right to get attention and love from their parents, then parents have an obligation to look after, educate and nurture their children (Beedasy et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%